2014
DOI: 10.1142/s175882511450029x
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Wrinkling of Thin Films on Pre-Stretched Elastomers Induced by Gravity

Abstract: We study wrinkling instability of a thin elastic film on a pre-stretched soft elastomer induced by the gravity of periodic array of the rods homogenously clamped on the surface of the film. By using linear perturbation analysis, we show that the periodic array of the rods can drive the wrinkling instability of the film when the gravitational force of the rods attains the threshold, and the film will wrinkle into stripes parallel to the tensile direction of the pre-stretched elastomer. Our calculation results g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…To further investigate the control of wrinkling patterns, they explored the potential of controlling gravity-induced wrinkles in thin films by subjecting the soft substrate to pre-stretching. [83] The results suggested that when the gravity of the pillars reaches a critical value, the wrinkles in the thin films form striped patterns parallel to the pre-tension direction. The wavelength of these patterns is determined not only by the bending stiffness of the film but also by the pre-stretch of the soft substrate.…”
Section: Wrinklesmentioning
confidence: 98%
“…To further investigate the control of wrinkling patterns, they explored the potential of controlling gravity-induced wrinkles in thin films by subjecting the soft substrate to pre-stretching. [83] The results suggested that when the gravity of the pillars reaches a critical value, the wrinkles in the thin films form striped patterns parallel to the pre-tension direction. The wavelength of these patterns is determined not only by the bending stiffness of the film but also by the pre-stretch of the soft substrate.…”
Section: Wrinklesmentioning
confidence: 98%